Development of a Microemulsion Formulation for Antimicrobial SecA Inhibitors - Hu, Jiahuai; Akula, Nagaraju; Wang, Nian (PLOS ONE, 2016)
In our previous study, we have identified five antimicrobial small molecules via structure based design, which inhibit SecA of Candidatus Liberibacter asiaticus (Las). SecA is a critical protein translocase ATPase subunit and is involved in pre-protein translocation across and integration into the cellular membrane in bacteria. In this study, eleven compounds were identified using similarity search method based on the five lead SecA inhibitors identified previously. The identified SecA inhibitors have poor aqueous solubility. Thus a microemulsion master mix (MMX) was developed to address the solubility issue and for application of the antimicrobials. MMX consists of N-methyl-2-pyrrolidone and dimethyl sulfoxide as solvent and co-solvent, as well as polyoxyethylated castor oil, polyalkylene glycol, and polyoxyethylene tridecyl ether phosphate as surfactants. MMX has significantly improved the solubility of SecA inhibitors and has no or little phytotoxic effects at concentrations less than 5.0% (v/v). The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the SecA inhibitors and streptomycin against eight bacteria including Agrobacterium tumefaciens, Liberibacter crescens, Rhizobium etli, Bradyrhizobium japonicum, Mesorhizobium loti, and Sinorhizobium meliloti phylogenetically related to Las were determined using the broth microdilution method. MIC and MBC results showed that the 16 SecA inhibitors have antibacterial activities comparable to that of streptomycin. Overall, we have identified 11 potent SecA inhibitors using similarity search method. We have developed a microemulsion formulation for SecA inhibitors which improved the antimicrobial activities of SecA inhibitors.